Bucillamine Prevents Afatinib-Mediated Inhibition of Epidermal Growth Factor Receptor Signaling - Naoyuki Nishiya; Moeka Murai; Ayumi Hosoda; Honami Yonezawa; Norikazu Omori (MDPI AG, 2019)
Molecular targeting therapies often cause characteristic adverse effects, such as skin rash during anti-epidermal growth factor receptor (EGFR) therapies, making treatment continuation difficult. In contrast, skin symptoms induced by EGFR inhibition are strongly correlated with the overall survival of the therapies. Therefore, controlling adverse effects not only facilitates treatment continuation but also increases clinical benefits. In this study, we proposed a novel strategy for reducing EGFR−tyrosine kinase inhibitor (TKI)-induced adverse effects in nontumorous organs by repositioning approved medicines using a zebrafish model. We developed a model system for evaluating chemical quenchers of afatinib, a clinically available irreversible EGFR-TKI, by scoring the inhibition of afatinib-induced hyperformation of lateral line neuromasts in zebrafish larvae. Bucillamine, an antirheumatic drug, was identified as an afatinib quencher in the zebrafish system and inhibited TKI activity in vitro. In addition, bucillamine restored EGFR autophosphorylation and downstream signaling in afatinib-treated A431 cells. Thus, topical bucillamine is a potential reliever of irreversible EGFR-TKI-induced skin rash. The zebrafish model can be applied to a screening for quenchers of other anti-EGFR-targeting therapies, including reversible TKIs and biologics.